Organoleptic Test of Healthy Turmeric Drinks in Combination with Clover - Yessita Puspaningrum (AGARICUS: Advances Agriculture Science & Farming, 2025)
Clover is generally used as a remedy for sore throat, mouth sores, fever, and shortness of breath.. This research was conducted to determine the process of making a healthy drink and organoleptic test from turmeric and clover. This study uses the RAL method withfive levels and four repetitions, so this study use twenty experimental units were obtained. Sample is made as K1 is clover 30%;turmeric 70%, K2 is clover 40%; tumeric 60%, K3 is clover 50%; tumeric 50%, K4 is clover 60%; turmeric 40%, K5 is clover 70%;tumeric 30%. Data analysis used descriptive, qualitative methods. The process of making healthy tumeric drinks combinationwith clover. Healthy tumeric drinks by mashing clover leaves and turmeric leaves, filtering, cooking until boiling then adding sugar, stirring slowly over medium heat, and speeding up the mix when it has clotted to get fine crystals. The cause of the color change is influenced by the crystallization temperature. The aroma of sugar caramel in the healthy drink of clover and turmeric and the taste is sweet. The acceptance variable is in great demand in the combination of 50% clover leaf K3 and 50% turmeric leaf.